Magnesium Elevation Promotes Neuronal Differentiation While Suppressing Glial Differentiation of Primary Cultured Adult Mouse Neural Progenitor Cells through ERK/CREB Activation - Liao, Wang; Jiang, Mujun; Li, Mei; Jin, Congli; Xiao, Songhua; Fan, Shengnuo; Fang, Wenli; Zheng, Yuqiu; Liu, Jun (Frontiers in Neuroscience, 2017)
This study aimed to explore the influence of magnesium elevation on fate determination of adult neural progenitor cells (aNPCs) and the underlying mechanism in vitro. Adult neurogenesis, which is the generation of functional neurons from neural precursors, occurs throughout life in restricted anatomical regions in mammals. Magnesium is the fourth most abundant ion in mammals, and its elevation in the brain has been shown to enhance memory and synaptic plasticity in vivo. However, the effects of magnesium on fate determination of aNPCs, which are vital processes in neurogenesis, remain unknown. NPCs isolated from the dentate gyrus of adult C57/BL6 mice were induced to differentiate in a medium with varying magnesium concentrations (0.6, 0.8, and 1.0mM) and extracellular signal–regulated kinase (ERK) inhibitor PD0325901. The proportion of cells that differentiated into neurons and glial cells was evaluated using immunofluorescence. Quantitative real-time polymerase chain reaction and Western blot methods were used to determine the expression of β-III tubulin (Tuj1) and glial fibrillary acidic protein (GFAP). The activation of ERK and cAMP response element–binding protein (CREB) was examined by Western blot to reveal the underlying mechanism. Magnesium elevation increased the proportion of Tju1-positive cells and decreased the proportion of GFAP-positive cells. Also, the expression of Tuj1 was upregulated, whereas the expression of GFAP was downregulated. Moreover, magnesium elevation enhanced the activation of both ERK and CREB. Treatment with PD0325901 reversed these effects in a dose-dependent manner. Magnesium elevation promoted neural differentiation while suppressing glial cell differentiation, possibly via ERK-induced CREB activation.